Assessing laboratory report writing skills of first entering bachelor of science students - Veldtman, Helga Delene (University of Limpopo, 2020)
Conventional laboratory report writing skills present an enormous challenge to first entering science students including the Bachelor of Science (BSc) students at Sefako Makgatho Health Sciences University (SMHSU). First entering students are expected to meet essential tertiary discourse requirements and standards consistent with their scientific community. The purpose of this study was to explore how content lecturers in cognate departments assess laboratory report writing skills of first entering BSc students. The research design was exploratory and a mixed approach was used. Students sat for a criterion-referenced test and interviews were conducted with content lecturers to collect data; quantitative basic statistical interrogation of the basic data points and post interview analysis were performed. Some of the key findings of this exploration was that most first entering BSc students are in a dire situation regarding the laboratory report writing genre; they are unable to communicate comprehensive and intelligible information in the written laboratory reports. Thus, content lecturers and English language lecturers from the Department of Language Proficiency (DLP) need to strategically collaborate in order to improve the performance of first entering BSc students.
Thesis (M. A. (English Studies)) --University of Limpopo, 2020
Keywords: Laboratory report writing skills; First entering students; Bachelor of science; Laboratory report writing; Report writing; Note-taking